The subjects of literary and artistic copyright - Bonadio, Enrico; Sappa, Cristiana; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2022)
"This accessible and innovative book examines to what extent copyright protects a range of subjects who are engaged in the creation and management of literary and artistic works, and how such subjects use copyright to protect their interests. Offering a complementary analysis, The Subjects of Literary and Artistic Copyright explores how copyright regulates the production and management of literature and art. The book examines the creators of literature and art, as well as market operators such as publishers and "managers" including museums, galleries, and universities. The perspectives offered cover a diverse range of subjects, and confront the regular contradictions and conflicts that occur within literary and artistic copyright interests. The chapters illustrate, via historical and empirical analysis, that established practices and traditional approaches to the management of copyright need to be revisited, in order to be more aligned with current social and technological frameworks. Providing a starting point for future research paths on copyright practices in art and literature, this insightful book will be of interest to legal academics looking to expand their knowledge of literary and artistic copyright. Law professionals with interests in intellectual property and art law will also benefit from its novel approach"--
Foreword -- Introduction / Enrico Bonadio and Cristiana Sappa -- Part I: Creators section a literature -- 1. The effects of copyrights on poets' and novelists' economic returns / Michela Giorcelli -- 2. Playwrights / Luke McDonagh 3. The fragility of freelancing: The impact of copyright law on modern journalism / Mary Catherine Amerine -- 4. Academic authors, copyright and dissemination of knowledge: A comparative overview / Marco Bellia and Valentina Moscon -- Section b art -- 5. Copyright protection for painters, sculptors and cartoonists / Rudy Capildeo, Chris Haywood and James Yow -- 6. Digital photographers: Trust, truth, and copyright in the digital age / Jessica Silbey -- 7. 'It's not you, it's me': Are designers and copyright a good match? / Ana Ramalho -- 8. Architecture and dysfunction / Xiyin Tang -- Part II: Managers and intermediaries -- 9. Publishers and copyright / Enrico Bonadio and Anele Simon -- 10. Libraries and copyright law in the 21st century / Maximiliano Marzetti -- 11. Capturing the uncapturable: The relationship between universities and copyright through the lens of the audio-visual lecture capture policies / Guido Noto La Diega, Giulia Priora, Bernd Justin Jütte and Léo Pascault -- 12. Museums as education facilitators: How copyright affects access and dissemination of cultural heritage / Cristiana Sappa -- 13. Galleries and auction houses: The invisible managers of artistic copyright? / Simon Stokes -- Index.
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: autorské právo; literární dílo; umělecké dílo; copyright; literary work; art work; e-knihy online; e-books online